To swing or not to swing: An assessment of age and political cynicism of swing voting - Damon Proulx; David Savage; David Stadelmann; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
The empirical question of voting preferences and how these may change (swing) is yet to be answered, as there is little first-hand microeconomic evidence on swing voting. We focus on the interactions between voters' age and political cynicism. Towards this end, we apply a stated and revealed preference framework to assess swing voting, using data from the Dutch Parliamentary Election Survey (DPES) 1989 to 2010. Our results indicate that swing voting is less likely to occur in older age groups and more likely among individuals with higher levels of political cynicism. The age effects tend to be stronger among those with lower political cynicism values.
Keywords: D72; D79; 330; swing voting; age; cynicism; elections